2022
DOI: 10.1002/jppr.1776
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort review of prescribing in hospitalised patients with heart failure using Beers criteria and STOPP recommendations

Abstract: Background With an ageing population and multimorbidity on the rise, polypharmacy is also increasing. Polypharmacy is common in patients with heart failure, possibly due to the application of evidence‐based therapy to improve prognosis and symptoms. Objectives To identify potentially inappropriate medications according to Beers criteria and the STOPP screening tool; To assess if the recommendations generated from applying these tools could have potentially unintended harmful outcomes in the context of a hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, deprescribing in HF has not been extensively studied. One small single-site study showed that when using published deprescribing tools to assess for inappropriate medications, the suggested outcomes generated recommendations that could have potentially detrimental effects on patients with HF 60…”
Section: Polypharmacymentioning
confidence: 99%
“…However, deprescribing in HF has not been extensively studied. One small single-site study showed that when using published deprescribing tools to assess for inappropriate medications, the suggested outcomes generated recommendations that could have potentially detrimental effects on patients with HF 60…”
Section: Polypharmacymentioning
confidence: 99%